Blood monocytes sample MelanA/MART1 antigen for long‐lasting cross‐presentation to CD8+ T cells after differentiation into dendritic cells. Issue 1 (26th September 2017) - Faure, Florence; Jouve, Mabel; Lebhar‐Peguillet, Isabelle; Sadaka, Charlotte; Sepulveda, Fernando; Lantz, Olivier; Berre, Stefano; Gaudin, Raphael; Sánchez‐Ramón, Silvia; Amigorena, Sebastian
Abstract : Human blood monocytes are very potent to take up antigens. Like macrophages in tissue, they efficiently degrade exogenous protein and are less efficient than dendritic cells (DCs) at cross‐presenting antigens to CD8 + T cells. Although it is generally accepted that DCs take up tissue antigens and then migrate to lymph nodes to prime T cells, the mechanisms of presentation of antigens taken up by monocytes are poorly documented so far. In the present work, we show that monocytes loaded in vitro with MelanA long peptides retain the capacity to stimulate antigen‐specific CD8 + T cell clones after 5 days of differentiation into monocytes‐derived dendritic cells (MoDCs). Tagged‐long peptides can be visualized in electron‐dense endocytic compartments distinct from lysosomes, suggesting that antigens can be protected from degradation for extended periods of time. To address the pathophysiological relevance of these findings, we screened blood monocytes from 18 metastatic melanoma patients and found that CD14 + monocytes from two patients effectively activate a MelanA‐specific CD8 T cell clone after in vitro differentiation into MoDCs. This in vivo sampling of tumor antigen by circulating monocytes might alter the tumor‐specific immune response and should be taken into account for cancer immunotherapy. Abstract : What's new? Dendritic cells are known to act as "antigen‐presenting cells" (APCs), which process tumor antigens and use them to prime and activate specific T cells. In this study, the authors found that monocytes can also take up tumor antigens, and can then differentiate into dendritic APCs, which can continue to stimulate tumor‐specific CD8+ T cells for a prolonged period of time. The authors conclude that this in vivo sampling of tumor antigen by circulating monocytes might alter the tumor‐specific immune response, and should be taken into account for cancer immunotherapy.